Apple Pomace as a Potential Source of Oxidative Stress-Protecting Dihydrochalcones - Ibrahim Rabeeah; Viktoria Gruber-Schmidt; Helen Murray; Negin Afsharzadeh; Renate Paltram; Silvija Marinovic; Hassan Zia; Olly Sanny Hutabarat; Mikko Hofsommer; Ana Slatnar; Christopher Schlosser; Karl Stich; et al. (Antioxidants)
Among fruits, the apple is unique for producing large amounts of the dihydrochalcone phloridzin, which, together with phloretin, its aglycone, is valuable to the pharmaceutical and food industries for its antidiabetic, antioxidant, and anticarcinogenic properties, as well as its use as a sweetener. We analysed the phloridzin concentration, total phenolic content, and antioxidant activity in the peel, flesh, seeds, juice, and pomace of 13 international and local apple varieties. In the unprocessed fruit, the seeds had the highest phloridzin content, while the highest total phenolic contents were mostly found in the peel. In processed samples, phloridzin and the total phenolic compounds especially were higher mostly in juice than in pomace. Moreover, the total phenolic content was much higher than the phloridzin content. Juice showed the highest antioxidant activity, followed by the peel and flesh. Across all samples, antioxidant activity did not directly correlate with phloridzin concentrations, suggesting that the antioxidant activity ascribed to phloridzin may need re-evaluation. In the Ferric Reducing Antioxidant Power (FRAP) assay, phloridzin only showed antioxidant activity at high concentrations when compared to its aglycone, phloretin. Considering the large amounts of apple juice produced by the juice industry, residual pomace is a promising source of phloridzin. For technical use, processing this phloridzin to phloretin would be advantageous.